Is Autosomal Dominant Polycystic Kidney Disease Becoming a Pediatric Disorder? - De Rechter, Stéphanie; Breysem, Luc; Mekahli, Djalila (Frontiers in Pediatrics, 2017)
Autosomal Dominant Polycystic Kidney Disease (ADPKD) affects 1 in 400 to 1000 live births, making it the most common monogenic cause of renal failure. Although no definite cure is available yet, it is important to affect disease progression by influencing modifiable factors such as hypertension and proteinuria. Besides this symptomatic management, the only drug currently recommended in Europe for selected adult patients with rapid disease progression, is the vasopressin receptor antagonist tolvaptan. However, the question remains whether these preventive interventions should be initiated before extensive renal damage has occurred. As renal cyst formation and expansion begins early in life, frequently in utero, ADPKD should no longer be considered an adult-onset disease. Moreover, the presence of hypertension and proteinuria in affected children has been reported to correlate well with disease severity. Until now, it is controversial whether children at-risk for ADPKD should be tested for the presence of the disease, and if so, how this should be done. Herein, we review the spectrum of pediatric ADPKD and discuss the pro and contra of testing at-risk children and the challenges and unmet needs in pediatric ADPKD care.